The Effects Of Self-Image Congruence On Consumers' Brand Preference And Satisfaction In The Mobile Phone Service Provider Market In Malaysia - Mah, Kenny Ying Fye (2003)
This study investigates the effect of self-image congruence on consumers' brand preference and satisfaction in the mobile phone service provider market in Malaysia. Self-image congruence means taht consumers express themselves by choosing brands whose personalities are perceived to be congruent with their own personalities.